Comparison of skin prick allergy test in urban and rural children - Fakhri Widyanto; Rita Evalina Rusli; Muhammad Ali; Melda Deliana; Lily Irsa; M. Sjabaroeddin Loebis (Paediatrica Indonesiana, 2011)
Background Children who grow up in rural areas have a lower incidence of atopy and other allergic manifestations than children in urban areas. Several recent studies have suggested that agricultural exposure may protect children from developing asthma and atopy, but these findings are inconsistent.Objective To examine an association between living in rural or urban areas and skin prick allergy test results in children and to detennine associated risk factors for atopy.Methods We conducted a cross-sectional study in Karo district (rural) and Medan (urban) in October-December 2009. We enrolled primary school children who had a history of atopy in their families. Skin prick testing was done on the volar side of the forearm and included eight aero-allergens: house dust mites, house dust, cotton, chicken feathers, cat dander, cockroaches, mould, and pollen. We analyzed the folloMng risk factors forassociation Mth atopy: tobacco smoke, pets, livestock exposure, and having older sibling(s).Results We recruited 49 children from the Karo district and 52 children from the city of Medan. There were significant associations between living in an urban area and positive skin prick test results for house dust mites and house dust compared to living in a rural area (P=0.04, 95% CI: 1.11 to 5.91; P=0.04, 95% CI: 1.13 to 12.45, respectively). The reverse was true for cockroach allergens (P=0.02, 95% CI: 0.16 to 0.81). Tobacco smoke and livestock exposure were associated Mth negative skin prick test results in rural children (P=O.03, 95% CI: 0.03 to 0.81 and P=0.002, 95% CI: 0.02 to 0.42, respectively). Multivariate analysis revealed that lack of livestock exposure was the major risk factor associated Mth any positive skin prick test results in rural children (P=0.004; 95% CI ; 0.02 to 0.49).Conclusion There were differing associations between living in rural and urban areas to various skin prick test results in children. Lack of livestock exposure was the risk factor associated with positive skin prick test results in rural children.